2013
DOI: 10.1016/j.bbmt.2013.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Body Mass Index but Not CXCL12 801 G/A Polymorphism Determine the Efficacy of Hematopoietic Cell Mobilization: A Study in Healthy Volunteer Donors

Abstract: Analyses of healthy donors of granulocyte colony-stimulating factor (G-CSF) mobilized hematopoietic stem and progenitor cells (HSPCs) and of patients undergoing autologous stem cell transplantation have suggested that individuals harboring the CXCL12-A allele mobilize a higher number of CD34 + HSPCs after G-CSF administration. We typed 463 healthy unrelated donors (376 men and 87 women) who had received daily subcutaneous injections at a mean dose of 7.36 ± 1.71 μg/kg G-CSF for 5 days for CXCL12 801 G/A using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 16 publications
5
30
2
Order By: Relevance
“…Recently published data have focused on the impact of genetic polymorphisms on the mobilization process. Two different groups have reported an association of the CLCX12‐3′A allele with a better CD34+ mobilization, although these results could not be confirmed by our group in a larger cohort of donors . Other genetic polymorphisms with potential impact include VCAM‐1 and CD44 .…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Recently published data have focused on the impact of genetic polymorphisms on the mobilization process. Two different groups have reported an association of the CLCX12‐3′A allele with a better CD34+ mobilization, although these results could not be confirmed by our group in a larger cohort of donors . Other genetic polymorphisms with potential impact include VCAM‐1 and CD44 .…”
Section: Discussioncontrasting
confidence: 84%
“…Two different groups have reported an association of the CLCX12-3 0 A allele with a better CD341 mobilization, 28,29 although these results could not be confirmed by our group in a larger cohort of donors. 30 Other genetic polymorphisms with potential impact include VCAM-1 and CD44. 31 Thus, greater effort to identify important genetic polymorphisms with functional or transcriptional activity is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an association between the SDF1-3 0 A allele and high levels of CD34 þ cell mobilization has been demonstrated in peripheral blood [22,24]. Recently, Lenk et al [25] reported no impact of SDF-1a 801G/A polymorphism on efficacy of HSC mobilization in the context of allogeneic healthy donors; their results are in line with our observation. However, the rate of UCB units released in our bank is approximately 10 units per year, and this did not allow us to perform an early study of engraftment kinetics of transplanted units provided from these 180 neonates evaluated by tetra-PCR.…”
Section: Resultssupporting
confidence: 93%
“…21,22 A recent report, however, found no significant effect of SCF-1 polymorphism on the mobilization efficiency in 467 healthy volunteer donors. 23 Currently, there are no published systematic investigations of genetic differences of these molecules among ethnic lines and further research in this area is warranted.…”
Section: Discussionmentioning
confidence: 99%